Corrosion casting in anatomy: Visualizing the architecture of hollow structures and surface details. (23rd May 2019) - Cornillie, Pieter; Casteleyn, Christophe; von Horst, Christoph; Henry, Robert
Abstract: Corrosion casting is the technique by which a solid, negative replica is created from a hollow anatomical structure and liberated from its surrounding tissues. For centuries, different types of hardening substances have been developed to create such casts, but nowadays, thermosetting polymers are mostly used as casting medium. Although the principle and initial set‐up are relatively easy, producing high‐quality casts that serve their intended purpose can be quite challenging. This paper evaluates some of the more popular casting resins that are currently available and provides a step‐by‐step overview of the corrosion casting procedure, including surface casts of anatomical structures. Hurdles and pitfalls are discussed, along with possible solutions to circumvent them, based on personal experience by the authors.